Nanocomposite Films of Chitosan-Grafted Carbon Nano-Onions for Biomedical Applications (2020)
The design of sca olding from biocompatible and resistant materials such as carbon nanomaterials and biopolymers has become very important, given the high rate of injured patients. Graphene and carbon nanotubes, for example, have been used to improve the physical, mechanical, and biological properties of di erent materials and devices. In this work, we report the grafting of carbon nano-onions with chitosan (CS-g-CNO) through an amide-type bond. These compounds were blended with chitosan and polyvinyl alcohol composites to produce films for subdermal implantation in Wistar rats. Films with physical mixture between chitosan, polyvinyl alcohol, and carbon nano-onions were also prepared for comparison purposes. Film characterization was performed with Fourier Transformation Infrared Spectroscopy (FTIR), Thermogravimetric Analysis (TGA), Di erential Scanning Calorimetry (DSC), Tensile strength, X-ray Di raction Spectroscopy (XRD), and Scanning Electron Microscopy (SEM). The degradation of films into simulated body fluid (SBF) showed losses between 14% and 16% of the initial weight after 25 days of treatment. Still, a faster degradation (weight loss and pH changes) was obtained with composites of CS-g-CNO due to a higher SBF interaction by hydrogen bonding. On the other hand, in vivo evaluation of nanocomposites during 30 days in Wistar rats, subdermal tissue demonstrated normal resorption of the materials with lower inflammation processes as compared with the physical blends of ox-CNO formulations. SBF hydrolytic results agreed with the in vivo degradation for all samples, demonstrating that with a higher ox-CNO content increased the stability of the material and decreased its degradation capacity; however, we observed greater reabsorption with the formulations including CS-g-CNO. With this research, we demonstrated the future impact of CS/PVA/CS-g-CNO nanocomposite films for biomedical applications.